Development of technology and research of gel with pentoxifylline - Nahornyi, V. V.; Nahorna, N. O.; Нагорний, Володимир Володимирович; Нагорна, Наталія Олександрівна (My University, 2022)
Abstract: The development of gel that meets modern requirements for the effectiveness and safety of a medicinal product the treatment of cardiovascular disease is a serious scientific study related to the selection of active and auxiliary substances, providing the necessary biopharmaceutical and rheological properties of the gel composition, standardizing the quality of the dosage form.
Keywords: pentoxifylline; gel; dispersion analysis; gel bases; method of equilibrium dialysis